- 1-214-256-5804
- info@tutorpace.com

In Substitution method, either ‘x’ or ‘y’ can be chosen to be written in terms of the other.

Given x+ y = 3==> y= 3 – x

Now substitute this value of ‘y’ in the second equation, x– y = 7.

This gives: x– (3 – x) = 7==>x– 3 + x = 7==> 2x= 7+ 3.

This gives: x= 10/2==> x = 5.

Now y = 3- x ==> y= 3– 5==> y = -2.

In Substitution method, either ‘x’ or ‘y’ can be chosen to be written in terms of the other.

Given x+ y = 5==> x= 5 – y

Now substitute this value of ‘x’ in the second equation, x– y = 1.

This gives: (5- y) – y = 1==> 5 – y – y = 1==> 5- 2y= 1==> 2y= 5- 1

This gives: y= 4/2==>y= 2.

Now x= 5- y==> x= 5– 2==>x= 3.